Nonsurgical management of horizontal root fracture associated external root resorption and internal root resorption - Shiraz Pasha; S Kusum Valli; Md Zaighum Raza (Wolters Kluwer Medknow Publications, 2016)
Horizontal root fractures, which frequently affect the upper incisors, usually result from a frontal impact. As a result, combined injuries occur in dental tissues such as the pulp, dentin, cementum, periodontal ligament, and alveolar bone. Internal root canal inflammatory resorption involves a progressive loss of intraradicular dentin without adjunctive deposition of hard tissues adjacent to the resorptive sites. It is frequently associated with chronic pulpal inflammation, and bacteria might be identified from the granulation tissues when the lesion is progressive to the extent that it is identifiable with routine radiographs. With the advancement in technology, it is imperative to use modern diagnostic tools such as cone beam computed tomography and radiovisuography to diagnose and confirm the presence and extent of resorptions and fractures and their exact location. This case report presents a rare case having internal root resorption and horizontal root fracture with external inflammatory root resorption both which were treated successfully following guidelines by International Association of Dental Traumatology by nonsurgical treatment with 1 year follow-up.